Quality of life in children and adolescents with primary headache disorders [Primer başağrısı olan çocuk ve ergenlerde yaşam kalitesi] - (:unkn) unknown (Ege University Press, 2016)
The frequency and significance of headache in children and adolescent has been drawing more attention nowadays. Similarly, growing body of data is being collected on the quality of life of headache in children and adolescent to which increased attention is paid. Compared with other chronic disorders, headache in children has more negative effect on school performance, as well as emotional status. As for school children, it is reported that these children could not go to school on a regular basis, they do less performance and their careers are negatively affected on the long-term. Accompanying symptoms such as depression, somatization, anxiety also impairs the quality of life. Early identification and treatment of headache will not only improve a health condition, but also will provide advancement in academic and social area as well as psychological development for children with headache. © 2016, Ege University Press. All right reserved.
Keywords: Children; Headache; Migraine; Quality of life; Tension type headache